Commissioning and initial experience with the first clinical gantry‐mounted proton therapy system. (8th March 2016) - Zhao, Tianyu; Sun, Baozhou; Grantham, Kevin; Rankine, Leith; Cai, Bin; Goddu, Sreekrishna M.; Santanam, Lakshmi; Knutson, Nels; Zhang, Tiezhi; Reilly, Michael; Bottani, Beth; Bradley, Jeffrey; et al.
Abstract : The purpose of this study is to describe the comprehensive commissioning process and initial clinical experience of the Mevion S250 proton therapy system, a gantry‐mounted, single‐room proton therapy platform clinically implemented in the S. Lee Kling Proton Therapy Center at Barnes‐Jewish Hospital in St. Louis, MO, USA. The Mevion S250 system integrates a compact synchrocyclotron with a C‐inner gantry, an image guidance system and a 6D robotic couch into a beam delivery platform. We present our commissioning process and initial clinical experience, including i) CT calibration; ii) beam data acquisition and machine characteristics; iii) dosimetric commissioning of the treatment planning system; iv) validation through the Imaging and Radiation Oncology Core credentialing process, including irradiations on the spine, prostate, brain, and lung phantoms; v) evaluation of localization accuracy of the image guidance system; and vi) initial clinical experience. Clinically, the system operates well and has provided an excellent platform for the treatment of diseases with protons. PACS number(s): 87.55.ne, 87.56.bd